Penerapan Analisis Regresi Spasial untuk Menentukan Faktor-Faktor Penyebab Stunting di Nusa Tenggara Barat Tahun 2021 - Vivi Suci Puspita; Teti Sofia Yanti (UNISBA Press, 2022)
Abstract. To find out a relationship based on location or place information, spatial regression analysis can be used. Spatial regression models include the General Spatial Model (GSM), Spatial Autoregressive Model (SAR) and Spatial Error Model (SEM). Mariana (2013) states that SEM is a model that has a spatial correlation on error, SAR is a model that has a spatial relationship on the dependent variable, and GSM is a combination of SEM and SAR models. The spatial weighting matrix is ​​the basic component of the spatial model, this matrix shows the relationship between one region and the surrounding area. The spatial weighting matrix used is the Queen Contiguity spatial weighting matrix. This study uses data on Stunting in West Nusa Tenggara in 2021. The data includes the number of Stunting toddlers as the dependent variable (Y) and there are five independent variables (X) namely the number of low birth weight babies, the number of toddlers receiving complete basic immunizations, the number of babies born receiving early initiation of breastfeeding, the number of babies receiving exclusive breastfeeding, and the number of infants receiving exclusive breastfeeding. poor people. The results show that the Spatial Autoregressive model is the best model, has the smallest Root Mean Square Error (RMSE) value. Based on the results of modeling with the Spatial Autoregressive Model (SAR) the factors that affect the number of Stunting toddlers in West Nusa Tenggara are the number of infants receiving Early Initiation of Breastfeeding and the number of infants receiving exclusive breastfeeding. Abstrak. Untuk mengetahui suatu hubungan berdasarkan informasi lokasi atau tempat dapat menggunakan analisis regresi spasial. Model regresi spasial di antaranya, yaitu General Spatial Model (GSM), Spatial Autoregressive Model (SAR) dan Spatial Error Model (SEM). Mariana (2013) menyebutkan bahwa SEM adalah model yang memiliki korelasi spasial pada galat, SAR merupakan model yang memiliki hubungan spasial pada variabel tak bebasnya, dan GSM merupakan gabungan dari model SEM dan SAR. Matriks pembobot spasial menjadi komponen dasar dari model spasial, matriks ini menunjukkan adanya hubungan antara satu wilayah dengan wilayah disekitarnya. Matriks pembobot spasial yang digunakan, yaitu matriks pembobot spasial Queen Contiguity. Penelitian ini menggunakan data Stunting di Nusa Tenggara Barat pada tahun 2021. Data meliputi jumlah balita Stunting sebagai variabel tak bebas ( ) dan terdapat lima variabel bebas ( ) yaitu jumlah bayi berat lahir rendah, jumlah balita mendapatkan imunisasi dasar lengkap, jumlah bayi lahir mendapat inisiasi menyusui dini, jumlah bayi mendapat ASI Ekslusif, dan jumlah penduduk miskin. Hasil penelitian menunjukkan bahwa model Spatial Autoregressive merupakan model terbaik, memiliki nilai Root Mean Square Error (RMSE) terkecil. Berdasarkan hasil pemodelan dengan model Spatial Autoregressive Model (SAR) faktor yang berpengaruh terhadap jumlah balita Stunting di Nusa Tenggara Barat yaitu jumlah bayi mendapat Inisiasi Menyusui Dini dan jumlah bayi mendapat ASI Ekslusif.